2022
DOI: 10.1139/apnm-2021-0517
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of nutrients and food categories in Canadian children and adolescents across levels of sugars intake: cross-sectional analyses of the Canadian Community Health Survey 2015 Public Use Microdata File

Abstract: Dietary recommendations to reduce sugars consumption may influence choices of sugars-containing foods and affect the intake of key micronutrients. We compared intakes of nutrients and food sources stratified by quintiles of total sugars in Canadian children (2-8y) and adolescents (9-13y, 14-18y) using 24-hour dietary recalls from the 2015 Canadian Community Health Survey-Nutrition. Energy intakes did not differ across quintiles of sugars intake. Those with lower sugars intakes (Q1/Q3) generally had higher prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…While increased consumption of dairy products may have replaced foods containing iron in the RDa group, the mean iron intake at the end of the intervention was not different between groups and was still above the EARs for females aged 9–13 and 14–18 years in both groups. Similarly, sugar intake decreased to a greater extent in LDa compared to RDa, which is consistent with a recent investigation demonstrating that dairy products contribute to increased total sugar intake in Canadian adolescents [ 49 ]. Importantly, dairy products are nutrient-dense contributors to total sugar intake in Canadian adolescents as opposed to confectionary and regular soft drinks (i.e., SSBs), and adolescents with mean intakes of total sugar had higher intakes of several nutrients important for growth and development that are found in dairy products, specifically potassium and calcium, compared to those with lower intakes of total sugar [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…While increased consumption of dairy products may have replaced foods containing iron in the RDa group, the mean iron intake at the end of the intervention was not different between groups and was still above the EARs for females aged 9–13 and 14–18 years in both groups. Similarly, sugar intake decreased to a greater extent in LDa compared to RDa, which is consistent with a recent investigation demonstrating that dairy products contribute to increased total sugar intake in Canadian adolescents [ 49 ]. Importantly, dairy products are nutrient-dense contributors to total sugar intake in Canadian adolescents as opposed to confectionary and regular soft drinks (i.e., SSBs), and adolescents with mean intakes of total sugar had higher intakes of several nutrients important for growth and development that are found in dairy products, specifically potassium and calcium, compared to those with lower intakes of total sugar [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Sixteen studies from 15 articles reported on associations between dietary intakes of sugar and fiber [ 13 , 14 , 16 , 17 , 19 , 22 , 24 , 25 , 26 , 27 , 30 , 31 , 33 , 36 , 38 ], and the results are presented in Supplemental Table S4 along with factors accounted for by each study’s design or analysis. Most of these studies (62.5%) were rated as moderate for potential bias (neutral ROB) due to the study design, but other studies that only had one dietary intake measure and that did not control for important confounders were rated as high for potential bias (poor ROB; see Supplemental Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…One remaining study analyzed both sugar and fiber as only absolute intakes (g) without controlling for energy [ 25 ]. Eight of the studies were conducted in child or adolescent populations [ 16 , 17 , 19 , 26 , 27 , 30 , 38 ] or reported separate results for participants under age 19 [ 14 ]. All other studies were conducted in adult populations [ 13 , 22 , 24 , 31 , 33 , 36 ] or combined adolescents and adults in analyses [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that, on average, US adolescents do not consume enough fruits, vegetables, and whole grains. Some studies have examined trends in specific nutrient intake like sugar, fiber, or potassium along with the associated health outcomes ( 24 , 25 ). However, few studies have attempted to characterize multi-nutrient patterns through clustering, and none have been carried out in adolescents.…”
Section: Discussionmentioning
confidence: 99%